Residential real estate analysis in Serbia - Vesna Martin (Anali Ekonomskog fakulteta u Subotici, 2023)
The aim of this paper is to analyse the residential real estate market in Serbia. Price movements in that part of the market affect price and financial stability equally, which are thus the main goals of most central banks. Previously, there was a gradual increase in the number of traded real estate, as well as an increase in real estate prices, with oscillations recorded during the second quarter of 2020 due to the COVID-19 virus pandemic. In this paper, we will present the available databases from the Serbian residential real estate market, as well as regulations that have been in place since the 2000s. The paper’s final section will examine whether there is a price bubble in this segment of the market by examining the long-term trend of the housing credit-to-GDP ratio using a one-sided Hodrick-Prescott filter with the parameter set to 400,000, as well as correlation and regression analysis. According to the analysis, there is currently no price bubble in Serbia’s residential real estate market.